Brazilian Higher Education in the 1960s and 1970s of the 20th Century: International Agreements and the Reform of the Brazilian University - Vechia, Ariclê; Gomes Ferreira, António (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2020)
After World War II, cooperation agreements in the educational area were signed between Brazil and the United States. However, from the 1960s, there was a closer relationship between the two countries, with new agreements signed between the Ministry of Education (MEC) and the United States Agency for International Development (USAID), known as the MEC-USAID Agreements. This study’s objective is to analyze the influence of the MEC-USAID Agreements on the reform of the university approved by Law 5.540 / 1968, which established norms for the organization and functioning of higher education. Regarding the methodology, it is a documentary and bibliographic study. The results indicate that although there are criticisms of the agreements, there is no denying that they had influence on the 1968 reform, mainly regarding the cathedra extinction as well as the teaching career institution and the adoption of the departmental regime and credits in subjects. In addition, the university structure established by Law 5.540 / 68 remains virtually unchanged to this day.